The transition from monocyte to tissue-resident macrophage requires DHPS - Gustavo E. Carrizo; Pianpian Lin; Seung Hyun Lee; Kevin Shenderov; Camille Blériot; Minsun Cha; Lena Schimmelpfennig; Zhen Shen; Nikki van Teijlingen Bakker; Katarzyna M. Grzes; Beth Kelly; Niloufar Safinia; et al. (Nature, 2026)
Abstract Tissue-resident macrophages (RTMs) form during embryogenesis, self-renew locally, and regulate tissue homeostasis by clearing dead cells and debris 1–6 . During tissue damage, however, bone-marrow-derived monocytes enter tissues and differentiate into RTMs, repairing the tissue and replenishing macrophages in the niche 1 . The universal cell-intrinsic mechanisms that control the monocyte-to-RTM transition and the maintenance of mature RTMs across tissues remain elusive 3 . Here we show that deoxyhypusine synthase (DHPS), an enzyme that mediates spermidine-dependent hypusine modification of translation factor eIF5A 5,7 , is required for RTM differentiation and maintenance. Mice with myeloid cell lack of DHPS ( Dhps -ΔM mice) had a global defect in RTMs across tissues, resulting in persistent but ultimately futile monocyte influx. Transcriptional analyses of DHPS-deficient macrophages indicated a block in their ability to differentiate into mature RTMs, whereas proteomics revealed defects in cell adhesion and signalling pathways. Sequencing of ribosome-engaged transcripts identified a subset of mRNAs involved in cell adhesion and signalling that rely on DHPS for efficient translation. Imaging of DHPS-deficient macrophages in tissues showed differences in morphology and tissue interactions, which were correlated with their failed RTM differentiation. DHPS-deficient macrophages were also defective in critical homeostatic RTM functions including efferocytosis and tissue maintenance. Together, our results demonstrate a cell-intrinsic, tissue-agnostic pathway that drives differentiation of monocyte-derived macrophages into RTMs.